2018
DOI: 10.2169/internalmedicine.0554-17
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Rectal Administration of Low-dose Diclofenac for the Prevention of Post-endoscopic Retrograde Cholangiopancreatography Pancreatitis

Abstract: Objective A 50-100-mg rectal dose of nonsteroidal anti-inflammatory drugs (NSAIDs; diclofenac or indomethacin) has been shown to prevent post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). However, this is higher than the recommended 25-mg dose that is commonly administered to Japanese patients. The objective of this study was to evaluate the safety and efficacy of 25-mg rectal dose of diclofenac in preventing PEP. Methods Between January 2016 and March 2017, a total of 147 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
(27 reference statements)
1
19
1
1
Order By: Relevance
“…14 Even a 25-mg rectal dose of diclofenac seems to reduce the rate of PEP in Japanese population. 15 However, another Japanese RCT demonstrated no evidence of the effectiveness of low-dose rectal diclofenac in decreasing the PEP rate in both low-and high-risk patients, 16 which is similar to the results of our analysis propensity score matching analysis. As with using 100 mg of NSAIDs, the preventive effect of the low-dose NSAIDs on PEP remains unproven.…”
Section: Discussionsupporting
confidence: 82%
“…14 Even a 25-mg rectal dose of diclofenac seems to reduce the rate of PEP in Japanese population. 15 However, another Japanese RCT demonstrated no evidence of the effectiveness of low-dose rectal diclofenac in decreasing the PEP rate in both low-and high-risk patients, 16 which is similar to the results of our analysis propensity score matching analysis. As with using 100 mg of NSAIDs, the preventive effect of the low-dose NSAIDs on PEP remains unproven.…”
Section: Discussionsupporting
confidence: 82%
“…Several previous studies have indicated that the use of low-dose rectal diclofenac [19,[35][36][37][38] and the performance of pancreatic stenting [39,40] effectively prevent PEP. The present study did not demonstrate the preventive effect of diclofenac and pancreatic stenting; however, the dose of diclofenac (50 mg, which might not have been enough for the prevention of PEP) and the performance of pancreatic stenting in the present study were limited only to patients who underwent several cannulations during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides for reduction of PEP rectal administration of NSAIDS is found to be effective in various study. 18 , 19 , 20 Mok SRS et al randomized, double blinded, placebo-controlled trial showed reduced incidence of PEP in ringer lactate plus rectal indomethacin versus normal saline plus placebo. 21 In our study we have also included NSAIDs (diclofenac intramuscular) in all cases however, various studies support effectiveness of NSAIDs given only per rectal compared to other routes.…”
Section: Discussionmentioning
confidence: 99%